The effectiveness of medical care to patients with asthma in Tomsk Region - O. S. Kobyakova; L. M. Ogorodova; L. V. Abashina; I. A. Deyev; E. A. Starovoytova (Бюллетень сибирской медицины)
A statistical study of indicators of primary and chronic morbidity, mortality, clinical examinations, emergency care, the level of hospitalization of patients with asthma in the Tomsk Region for the years 1998—2008 was performed. This study used data of 843 thousand inhabitants of the Tomsk Region in the age of 18 years.During 1998—2008 in the Tomsk Region has made significant progress in the conduct of asthmatic patients, which is reflected in the cost of health care and higher quality care this patient.